CREB Regulates Experience-Dependent Spine Formation and Enlargement in Mouse Barrel Cortex - Annabella Pignataro; Antonella Borreca; Martine Ammassari-Teule; Silvia Middei (Neural Plasticity)
Experience modifies synaptic connectivity through processes that involve dendritic spine rearrangements in neuronal circuits. Although cAMP response element binding protein (CREB) has a key function in spines changes, its role in activity-dependent rearrangements in brain regions of rodents interacting with the surrounding environment has received little attention so far. Here we studied the effects of vibrissae trimming, a widely used model of sensory deprivation-induced cortical plasticity, on processes associated with dendritic spine rearrangements in the barrel cortex of a transgenic mouse model of CREB downregulation (mCREB mice). We found that sensory deprivation through prolonged whisker trimming leads to an increased number of thin spines in the layer V of related barrel cortex (Contra) in wild type but not mCREB mice. In the barrel field controlling spared whiskers (Ipsi), the same trimming protocol results in a CREB-dependent enlargement of dendritic spines. Last, we demonstrated that CREB regulates structural rearrangements of synapses that associate with dynamic changes of dendritic spines. Our findings suggest that CREB plays a key role in dendritic spine dynamics and synaptic circuits rearrangements that account for new brain connectivity in response to changes in the environment.